Relationship Between the Paraoxonase 1 Gene Glutamine 192 to Arginine Polymorphism and Diabetes Mellitus in Ghanaian Subjects - Aryee, Nii A.; Asante-Poku, Steve A.; Tagoe, Emmanuel A.; Ababio, Grace K.; Annan, Dorcas A. Muhyia (International Journal of Innovative Research in Medical Science, 2025)
Introduction: The activity of human Paraoxonase 1 (PON1), an HDL-associated enzyme with anti-atherogenic properties, has been observed to be reduced in a number of diseases, including diabetes. This has partly been attributed to a PON1 Glutamine (Q)/Arginine (R) polymorphism at codon 192 of the PON1 gene. Aim: To determine the prevalence of PON1 Q192R polymorphism in Ghanaian patients with type 2 diabetes (T2DM), and it impact on lipid profiles of T2DM subjects. Methods: PON1 Q192R was genotyped in 112 individuals with type 2 diabetes mellitus (T2DM) and 97 nondiabetic control individuals, using polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP) analysis. Other investigations determined using standard methods included fasting blood glucose (FPG), body mass index (BMI), lipid profile, atherogenic indices and hip-waist ratios. Results: The PON1 RR genotype found to be was the most common in both T2DM patients (74.6 %) and controls (57.1 %), whilst the QR genotype was the least frequent in both groups (7.3 % and 9.5% for T2DM and controls respectively). These genotype distributions were however not significantly different between the study groups. Allele frequencies in T2DM and the control groups were significantly different, with R allele being the most common in both T2DM patients and controls. The R allele was found to be increased in T2DM. The Q192R genotype does not consistently affect the lipid and lipoprotein concentrations of T2DM and healthy populations. Conclusion: The RR genotype was the most predominant in T2DM patients and healthy individuals within a Ghanaian population. The prevalence of the R allele in T2DM may have implications for the metabolism of oxidized lipoproteins as these oxidative modifications are central to the development of cardiovascular disease in T2DM.